Informed consent procedures for pregnant women before undergoing caesarean section at Donald Fraser Hospital, Limpopo Province, South Africa - Kwinda, Munyadziwa Albert (University of Limpopo ( Medunsa Campus ), 2010)
nformed consent procedures in pregnant women before undergoing caesareaction at Donald Fraser Hospital, Limpopo Province, South Africa Aim: To determine the adequacy of information received by pregnant women before undergoing caesarean section Study Design: Cross – sectional descriptive quantitative study Setting: Donald Fraser Hospital maternity ward Methods: 128 patients where surveyed using a standardized questionnaire 2 – 3 days after caesarean section. The study extended from November 2009 to May 2010. Data was collected by a trained research assistant. The data entered on the questionnaire was entered and frequencies and percentages were analyzed on Stata. Results: 126(98.44%) admitted that they were informed of the reason why a caesarean section had to be performed and 124(98.41) could recall the information provided. 108(84.38%) of participants admitted to being informed about the benefits of having a caesarean section as a mode of delivering their babies, however, only 7(6.48%) participants remembered the information provided. 6(4.69%) and 3(2.34%) of the participants admitted to being informed about complications that may occur during and after caesarean section, respectively; and 33.33% could recall the information provided for both. 50(39.06%) admitted to being informed about the implications of the caesarean section to future pregnancies and 12(24%) could remember the information provided. Majority of participants, 124(96.88%) admitted to being informed about the type of anaesthesia to be administered, however, 89(71.77%) could remember the information provided and 10(7.81%) were informed about the viii possible complications of anaesthesia although only 4(40%) could remember the information provided. The strength of association between participants’ profile and their responses was generally weak, except those with previous caesarean section and their responses to the question that seek to understand if they were informed about the future implications of the caesarean section to future pregnancies. Conclusions: Pregnant women are not informed about the complications or risks associated with caesarean section and anaesthesia to be administered. This makes informed consent procedures to be inadequate.
Thesis ( M Med (Family Medicine))--University of Limpopo, 2010.
Keywords: Cesarean section